Multisensory temporal order judgments: when two locations are better than one. - Spence, C; Baddeley, R; Zampini, M; James, R; Shore, D (2003)
In Experiment 1, participants were presented with pairs of stimuli (one visual and the other tactile) from the left and/or right of fixation at varying stimulus onset asynchronies and were required to make unspeeded temporal order judgments (TOJs) regarding which modality was presented first. When the participants adopted an uncrossed-hands posture, just noticeable differences (JNDs) were lower (i.e., multisensory TOJs were more precise) when stimuli were presented from different positions, rather than from the same position. This spatial redundancy benefit was reduced when the participants adopted a crossed-hands posture, suggesting a failure to remap visuotactile space appropriately. In Experiment 2, JNDs were also lower when pairs of auditory and visual stimuli were presented from different positions, rather than from the same position. Taken together, these results demonstrate that people can use redundant spatial cues to facilitate their performance on multisensory TOJ tasks and suggest that previous studies may have systematically overestimated the precision with which people can make such judgments. These results highlight the intimate link between spatial and temporal factors in determining our perception of the multimodal objects and events in the world around us.